Association of inflammation with worsening HOMA-insulin resistance - Park, K. (Diabetologia, 2009)
AIMS/HYPOTHESIS: We examined the cross-sectional and longitudinal relationships between C-reactive protein (CRP), a marker of low-grade inflammation, and insulin resistance and whether the association was independent of obesity and oxidative stress. METHODS: CRP and insulin resistance (homeostasis model assessment of insulin resistance [HOMA-IR]) data were obtained in a population-based, prospective observational study, Coronary Artery Risk Development in Young Adults (CARDIA), during 1992–2006. RESULTS: CRP showed a significant positive association with insulin resistance, both cross-sectionally and longitudinally (5 year follow-up). The estimated increment in HOMA-IR was 0.34 log(e)(pmol/l×[mmol/l]/156.25) (p value for trend <0.0001) in the highest vs lowest CRP quartiles in cross-sectional analysis, whereas the corresponding estimate was 0.12 (p trend <0.0001) in the highest vs lowest CRP quartiles longitudinally over 5 years. The gradient of HOMA-IR across CRP was attenuated but remained statistically significant after controlling for body fat measurements (0.06 in the highest vs lowest CRP in both cross-sectional [p value for trend=0.001] and longitudinal analyses [p value for trend=0.01]), and was little changed by further adjustment for oxidative stress markers (F(2)-isoprostanes and oxidised LDL). There were consistent increments in the levels of HOMA-IR with increasing concentrations of CRP over time. In contrast, higher HOMA-IR did not predict future increases in CRP. Findings were similar using fibrinogen as the predictor variable. CONCLUSIONS/INTERPRETATION: Although a substantial portion of this association was explained by obesity, CRP was independently related to concurrent and future insulin resistance.